Pulse seeds: current situation and perspectives (Research, Society and Development, 2021)
Pulse seeds are dry seeds from pulses, which are of global importance due to the benefits they bring to health, these seeds move the economic market both domestically and abroad due to the growing demand from both India and other countries. For this reason, this literature review aims to describe the scenario and production and marketing of pulses seeds of lentil, beans, chickpeas and peas. Regarding the current situation of these pulses seeds mentioned above, there is little demand for pulses seeds and people have a certain dietary preference for specific types of pulses, price and availability in the market, as shown by the results presented in this paper, in relation the perspective is that pulses seeds will double its production over the years due to high demand, demand and more affordable prices.